The effect of wearing masai barefoot technology shoes on recovery after marathon running - Nakagawa, K.; Inami, T.; Yonedu, T.; Kenmotsu, Y.; Narita, T.; Kawakami, Y.; Kanosue, K. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: A fast recovery from post-full marathon fatigue enables to stay good condition for training as well as for daily life. We previously reported that unstable rocker shoes (asai Barefoot Technology: MBT) can promote fast recovery in the subjective fatigue from marathon running (Nakagawa et al. 2014). However, it was questionnaire study, and not based on objective indexes. The purpose of the present study was to investigate whether MBT shoes can promote recovery from marathon based on muscle damage markers. Methods: The 25 university students participated in the study. They were divided into two groups and wore MBT shoes (MBT group, n=11) or ordinary shoes (control group, n=14) from immediately after marathon (42.195 km) for 1 weeks later. Before (Pre), immediately (Post), 1 day (D1), 3 days (D3) and 8 days (D8) after marathon, muscle hardness (ultrasound elastography), isometric muscle force, muscle soreness and subjective fatigue were measured. Number of steps per day in recovery period was also measured. For each index, the difference between post or D1 and D3 or D8 was calculated as the magnitude of recovery. Results There was no statistical group difference in marathon time and number of steps per day in recovery period. The magnitude of recovery of muscle hardness of gastrocnemius, knee extension force and subjective fatigue were significantly higher in the MBT group compared to the control group. Discussion: The result of subjective fatigue had similar tendency to that in our previous study. In addition, we found that muscle hardness and force in some muscles recovered faster in the MBT group. It has been reported that electromyographic activities in lower limb muscles including gastrocnemius and RF were higher during standing or walking with wearing the MBT (Nigg et al. 2012). This activity could become an active rest for lower-limb muscles with heavy damages. In conclusion, wearing MBT shoes can be effective for the recovery of muscle hardness and muscle force from marathon-induced damages.